PEMBINAAN MAHASISWA SECARA DARING DALAM PENYELENGGARAAN KEGIATAN WEBINAR NASIONAL PEMASARAN PADA MASA PENDEMI COVID-19 - Desi Susanti; Sri Mulyana; Nefrida (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
ABSTRACT: Webinars are an alternative taken by agencies/organizations to provide information and knowledge during the pandemic COVID-19. Although webinars are often held by agencies or organizations, few are held by students. This community service aims to foster students to be able to organize webinar activities during the pandemic COVID-19. This activity was attended by 15 final semester students who were selected based on their interests and talents. The selection of participants by convenience sampling technique. Before and after the service activities, interviews and questionnaires were distributed to participants. The results of the interviews before the webinar revealed that none of the participants had experience in hosting a webinar, and only 27% thought that the webinar could be held. After the service activities were carried out, all participants (100%) stated that this service activity was useful. and has honed the hard skills and soft skills of students that were not obtained during lectures.